Exploring the alterations and function of skin microbiome mediated by ionizing radiation injury - Huang, Biao; An, Lu; Su, Wenxing; Yan, Tao; Zhang, Haifang; Yu, Dao-Jiang (Frontiers in Cellular and Infection Microbiology, 2022)
Background Radiation-induced skin injury (RISI) is still the most common and severe side effect of radiotherapy. The role of the skin’s microbial barrier in the pathogenesis and progression of RISI needs to be fully investigated. Methods This study aimed to explore the alterations in and functions of the skin microbiota in RISI. We applied the unculturable approach to characterize the cutaneous microbiomes of a radiation-induced animal model by sequencing the V1–V3 regions of the 16S ribosomal RNA (rRNA) gene. Combined with the downloaded clinical data of patients, a comprehensive analysis was performed to identify potential radioprotective species and metabolic pathways. Results There were no significant differences in the alpha diversity indices (Sobs, Shannon, Simpson, Ace, and Chao) between the acute radiation injury and control groups. Phylum-level analysis of the RISI microbiomes exhibited significant predominance of Firmicutes (mean abundance = 67%, corrected p = 0.0035). The high abundance of Firmicutes was significantly associated with rapid healing of RISI (average relative abundance = 52%; Kruskal–Wallis: p = 5.7E−4). Among its members, Streptococcus, Staphylococcus, Acetivibrio ethanolgignens group, Peptostreptococcus, Anaerofilum, and UCG-002 [linear discriminant analysis (LDA) > 3, p < 0.05] were identified as the core genera of Firmicutes. In addition, Lachnosiraceae and Lactobacillus occupied an important position in the interaction network (r > 0.6, p < 0.05). The differential metabolic pathways of RISI were mainly associated with carbohydrate metabolism (butanoate and propanoate metabolism), amino acid metabolism (tryptophan and histidine metabolism), energy metabolism, and lipid metabolism (fatty acid degradation and biosynthesis). Conclusion This study provides new insights into the potential mechanism and skin microbial changes in the progression of RISI. The overwhelming predominance of members of Firmicutes, including Streptococcaceae, Staphylococcaceae, Lachnospiraceae, and Lactobacillus, is potentially related to rapid healing of RISI. The microbiota–metabolite axis plays a critical role in RISI and provides promising therapeutic targets for the treatment of adverse side effects.